Enantioselective Reactions of Redox-Active Esters Catalyzed via Cooperative Photoredox/Chiral Phosphoric Acid Catalysis - Moon, Junsoo; Lee, Sujin; Shin, Eunjoo; Kwon, Yongseok (Synthesis, 2025)
Redox-active esters have garnered significant interest owing to their bench stability and photochemical reactivity. When combined with photoredox and chiral phosphoric acid catalysis, these esters enable the formation of new carbon–carbon bonds while concurrently inducing chirality. Since the pioneering enantioselective Minisci-type addition reported by Phipps, substantial progress has been achieved in this promising field. This review summarizes the developments and mechanistic insights accumulated over the past decade, offering perspectives on future research directions.
Keywords: Asymmetric catalysis; Chiral phosphoric acid; Friedel−Crafts reaction; Minisci reaction; Photoredox catalysis; Radical reaction; Redox-active ester